ILLOCUTIONARY ACTS OF MILES MORALES IN “SPIDER-MAN: INTO THE SPIDER-VERSE”: IDENTITY REPRESENTATION THROUGH SPEECH ACTS - Pipit, Mayang; Hafifah, Sarah (IdeBahasa, 2025)
This study aims to identify and analyze the illocutionary speech acts performed by the main character, Miles Morales, in the animated film Spider-Man: Into the Spider-Verse, and to interpret how these acts contribute to the construction of his identity. The data source consists of Miles Morales’ utterances throughout the film. The study applies Searle’s classification of speech acts as its theoretical framework, which includes five categories: assertive, directive, expressive, commissive, and declarative. Using a qualitative descriptive method within a pragmatic approach, data were collected through careful observation and transcription of relevant dialogue. The collected utterances were then classified and analyzed based on the five types of illocutionary acts. The findings are presented in the form of percentages to show the distribution of each speech act category. The results indicate that assertive (36%) and expressive (32%) acts are the most frequently used, followed by directive (28%) and commissive (4%), with no declarative acts identified. These findings suggest that Miles Morales constructs his identity largely through statements of belief and emotional expression, reflecting a character in emotional transition and self-discovery. Therefore, illocutionary acts in this film not only serve pragmatic functions but also play a crucial role in representing character identity within popular media narratives.